Clinical Features and Molecular Analysis of Hb H Disease in Taiwan. (28th August 2014) - Chao, Yu-Hua; Wu, Kang-Hsi; Wu, Han-Ping; Liu, Su-Ching; Peng, Ching-Tien; Lee, Maw-Sheng
Abstract : Thalassemia is highly prevalent in Taiwan, but limited data are available about the association between genotypes and clinical manifestations in Taiwanese patients with Hb H disease. Here, we studied α-globin gene abnormalities and clinical features in Taiwanese patients with Hb H disease. Of the 90 patients, sixty-four (71.1%) were deletional and twenty-six (28.9%) were nondeletional Hb H disease. The (- - SEA ) type of α 0 -thalassemia mutation was detected in the majority of patients (>95%). The most common genotype was (- - SEA / - α 3.7 ), followed by (- - SEA / α cs α ). After further investigation of the genotype-phenotype correlation in 68 patients, we found that patients with nondeletional Hb H disease had more severe clinical features than those with deletional Hb H disease, including younger age at diagnosis, more requirement of blood transfusions, and larger proportion of patients with splenomegaly, hepatomegaly or jaundice. This is probably a consequence of the lower hemoglobin levels and the higher Hb H levels. The clinical severity was highly variable even among patients with an identical genotype, and the diversity was much more profound among patients with (- - / α cs α ) genotype. Therefore, predicting the phenotype directly from the genotype in Hb H disease remains relatively difficult in Taiwan.